Utilising authentic production data in a psycholinguistic-based study on code-switching: a conceptual paper - Chong, Yin Sheun; Khazriyati Salehuddin; Bahiyah Abdul Hamid (Penerbit Universiti Kebangsaan Malaysia, 2023)
Code-switching is especially common within the Southeast Asian region which is home to a large number of bilinguals and multilinguals. Over the years, code-switching has been studied extensively, both in and out of Asia, via sociolinguistics, structural linguistics, and psycholinguistics. From the psycholinguistic perspective, code-switching is said to be the result of the co-activation of languages during the process of speech production for bilinguals. Grosjean’s Language Mode and Green’s Control Process Model are two psycholinguistic frameworks focusing on the psycholinguistic as well as interactional factors behind code-switching. However, past studies in this area were mostly experimental in nature. It is necessary to consider authentic production data to develop a greater understanding of the code-switching phenomenon especially within the Southeast Asian context due to its bilingual and multilingual communities. This conceptual paper aims to demonstrate how the interactional and psycholinguistic factors behind code-switching can be examined using authentic production data. In particular, a review of the literature pointed to the Conversation Analysis (CA) approach to code-switching as well as the concepts of triggered code-switching and primed code-switching as being relevant. Accordingly, this paper describes each construct in detail and provides suggestions on how they can be brought together in a single study on code-switching based on authentic production data.